2015
DOI: 10.18632/oncotarget.4496
|View full text |Cite
|
Sign up to set email alerts
|

Detection of soluble EpCAM (sEpCAM) in malignant ascites predicts poor overall survival in patients treated with catumaxomab

Abstract: EpCAM is an attractive target for cancer therapy and the EpCAM-specific antibody catumaxomab has been used for intraperitoneal treatment of EpCAM-positive cancer patients with malignant ascites. New prognostic markers are necessary to select patients that mostly benefit from catumaxomab. Recent data showed that soluble EpCAM (sEpCAM) is capable to block the effect of catumaxomab in vitro. This exploratory retrospective analysis was performed on archived ascites samples to evaluate the predictive role of sEpCAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Serum levels of EpEX in tumor patients revealed low [ 46 , 110 , 112 – 114 ] but represent systemic levels, which suggests substantially higher intratumoral levels at the interface of tumor cells, where EpEX is actively shed [ 115 ]. Hence, production of EpEX by carcinoma cells could locally impact the regulation of EGFR-dependent proliferation and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of EpEX in tumor patients revealed low [ 46 , 110 , 112 – 114 ] but represent systemic levels, which suggests substantially higher intratumoral levels at the interface of tumor cells, where EpEX is actively shed [ 115 ]. Hence, production of EpEX by carcinoma cells could locally impact the regulation of EGFR-dependent proliferation and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that patients with soluble EpCAM present in ascites had a significantly shorter overall survival; the prognostic significance was particularly strong in patients with ovarian cancer. However, puncture-free survival and time to next puncture were not significantly different between soluble EpCAM-positive and -negative patients [ 128 ].…”
Section: Palliative Treatment For Malignant Ascitesmentioning
confidence: 99%
“…Hence, Amgen is currently advancing new versions of BiTE molecules by fusing the Fc domain. However, the fact that catumaxomab, a bispecific mAb for CD3, and EpCAM have been withdrawn due to toxicity issues, presumably because of FcγR or C1q binding of Fc [125][126][127][128] , indicates that for T-cell engagers, FcγR-related effector functions are detrimental with respect to clinical aspects. Therefore, simple Fc fusion for half-life extension purposes may lead to side effects, such as toxicity and/or shortened efficacy, at least in case of BiTE.…”
Section: Engineering Valency or Bispecificity Of Antibodiesmentioning
confidence: 99%